Frailty and Sarcopenia: Impact on Outcomes Following Elective Degenerative Lumbar Spine Surgery. Issue 20 (15th October 2022) - Chotai, Silky; Gupta, Rishabh; Pennings, Jacquelyn S.; Hymel, Alicia M.; Archer, Kristin R.; Zuckerman, Scott L.; Stephens, Byron F.; Abtahi, Amir M.
Abstract : Study Design: This is a retrospective review of prospectively collected data. Objective: The aim was to evaluate the impact of frailty and sarcopenia on outcomes after lumbar spine surgery. Summary of Background Data: Elderly patients are commonly diagnosed with degenerative spine disease requiring surgical intervention. Frailty and sarcopenia result from age-related decline in physiological reserve and can be associated with complications after elective spine surgery. Little is known about the impact of these factors on patient-reported outcomes (PROs). Methods: Patients older than 70 years of age undergoing elective lumbar spine surgery were included. The modified 5-item frailty index (mFI-5) was calculated. Sarcopenia was defined using total psoas index, which is obtained by dividing the mid L3 total psoas area by VB area (L3-TPA/VB). PROs included Oswestry disability index (ODI), EuroQual-5D (EQ-5D), numeric rating scale (NRS)-back pain, NRS leg pain (LP), and North American Spine Society (NASS) at postoperative 12 months. Clinical outcomes included length of stay (LOS), 90-day readmission and complications. Univariate and multivariable regression analyses were performed. Results: Total 448 patients were included. The mean mFI-5 index was 1.6±1.0 and mean total psoas index was 1.7±0.5. There was a significant improvement in all PROs from baseline to 12 months ( P <0.0001). After adjusting for age, body mass index, smoking status, levels fused, and baseline PROs, higher mFI-5 index was associated with higher 12-month ODI ( P <0.001), lower 12-month EQ-5D ( P =0.001), higher NRS-L P ( P =0.039), and longer LOS ( P =0.007). Sarcopenia was not associated with 12-month PROs or LOS. Neither sarcopenia or mFI-5 were associated with 90-day complication and readmission. Conclusions: Elderly patients demonstrate significant improvement in PROs after elective lumbar spine surgery. Frailty was associated with worse 12 months postoperative ODI, EQ-5D, NRS-LP scores, and longer hospital stay. While patients with sarcopenia can expect similar outcomes compared with those without, the mFI-5 should be considered preoperatively in counseling patients regarding expectations for disability, health-related quality of life, and leg pain outcomes after elective lumbar spine surgery. Level of Evidence: 3.